Sosialisasi Pengurangan Pajak Bumi dan Bangunan bagi Warga Masyarakat Tidak Mampu - Andi Yusuf Katili; Luthfia Bakari; Agus Pariono; Delvianty Ahmad (Gapenas Publisher, 2023)
The obligation to pay taxes is one that must be carried out by citizens who own and control land and buildings in an area, without compensation or reciprocity and are coercive. Taxes are levies in the form of fees charged by the government to citizens. Because taxes are one of the state revenues, the awareness of citizens to pay off their tax debts must continue. The purpose of this Community Service activity (PkM) is to provide an understanding that the government is based on applicable laws and regulations, specifically Mayor Regulation Number 17 of 2019 concerning the Provision of Rural and Urban PBB Stimulus in Gorontalo City for residents who can't afford it by making an application. The method used in this activity is counseling or outreach regarding land and building tax deductions for residents who can't afford it. The location for the implementation of the PkM activities took place at the Liluwo Village Office, Kota Tengah District, Gorontalo City, which was carried out for one day attended by 45 residents who have had difficulty paying PBB because the tax burden continues to increase, while taxpayers do not have a steady income. With this socialization or counseling activity, it is hoped that residents will be obliged to understand and be aware of paying PBB after receiving a stimulus or reduction